Plural Identities and Customary Governance in East Seram: The Persistence of Negeri Institutions - Syarifudin Syarifudin (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This article examines the cultural identity, territorial claims, and adat governance of negeri communities in East Seram, Maluku. Conducted by Gaia Indonesia in January–February 2024, the research focused on twelve villages located around a forestry concession area, representing three typologies: coastal negeri historically linked to the Tidore Sultanate, mountain negeri of the Alifuru people, and state-built transmigration villages. Using ethnographic methods—interviews, focus group discussions, participant observation, and participatory mapping—the study explored oral histories, adat institutions, sacred sites, and land disputes. The findings show that negeri cannot be reduced to an administrative category but remain living institutions that shape social life, cultural identity, and territorial governance. Coastal negeri such as Waru and Belis emphasize legitimacy through Tidore recognition and maritime networks, while mountain negeri such as Boinfia, Gah, and Solang ground identity in ancestral myths, sacred landscapes, and adat rules. Transmigration villages, by contrast, derive legitimacy from state law and development programs. Tensions emerge where adat boundaries diverge from administrative village borders, creating overlapping claims and the potential for horizontal conflict, particularly when external actors such as logging concessions intervene. This study contributes to anthropological debates on identity and space by showing how cultural identity in East Seram is plural, negotiated, and historically situated. Negeri institutions persist as resilient frameworks through which communities articulate belonging, authority, and rights to land.